Influência da sociedade no desenvolvimento tecnológico: um estudo das concepções de graduandos brasileiros do Estado de São Paulo - Veraszto, Estéfano Vizconde; Silva, Dirceu da; Barros Filho, Jomar; Miranda, Nonato Assis de; García, Francisco García; Amaral, Ségio Ferreira do; Simon, Fernanda Oliveira; Camargo, Eder Pires de [UNESP] (My University, 2011)
Trying to understand how society influences the individuals’ views and attitudes towards technological development, we have developed a theoretical model, transformed into a Likert scale to be applied to undergraduates Brazilians in Sao Paulo State. The data analysis, using Structural Equation Modeling (SEM), showed that the surveyed sample indicates the government, educational and research institutions, companies and citizens, as social actors strictly responsible for technology choices. The data also helped to establish the initial bases for the discussion of public policies in education, making room for further work on technological education.

Buscando compreender como a sociedade influencia nas concepções e atitudes dos indivíduos frente ao desenvolvimento tecnológico, desenvolveu-se um modelo teórico, traduzido em escala Likert para aplicação com graduandos brasileiros do Estado de São Paulo. A análise dos dados, através de Modelagem de Equações Estruturais (SEM), permitiu concluir que a amostra pesquisada aponta o governo, as instituições educacionais e de pesquisa, as empresas e os cidadãos, como os atores sociais estritamente responsáveis pelas escolhas tecnológicas. Os dados também permitiram estabelecer bases iniciais de discussão de políticas públicas educacionais, abrindo espaço para trabalhos futuros sobre educação tecnológica.
Influence of society on technological development: a study on the conceptions of Brazilian undergraduates in São Paulo State
Keywords: Technology; Society; Indicators of public perception; Structural equation modeling; Tecnologia; Sociedade; Idicadores de percepção pública; Modelagem de equações estruturais